Respuesta :

Answer:

Step-by-step explanation:

Solution by completing the square for:

x2−12x+9=0

Keep x terms on the left and move

the constant to the right side

by subtracting it on both sides

x2−12x=−9

Take half of the x term and square it

[−12⋅1/2]^2=36

then add the result to both sides

x^2−12x+36=−9+36

Rewrite the perfect square on the left

(x−6)^2=−9+36

and combine terms on the right

(x−6)^2=27

Take the square root of both sides

x−6=±27−−√

Simplify the Radical term (1):

x−6=±3–√3

Isolate the x on the left side and

solve for x (1)

x=6±3–√3

therefore (2)

x=6+3–√3

x=6−3–√3

which becomes

x=11.1962

x=0.803848